Effectiveness of A Psychological Counseling Program To Enhance Sports Cohesion Of Football Players - Baqi, Omar Nather Thanoun Abdul; Hamed, Nashwan Muhammad Sheet (Program Studi Pendidikan Kepelatihan Olahraga, 2025)
The current study aimed to build a psychological counseling program and identify the level of sports cohesion among the players of Mosul Municipality Club and Al-Amwaj Sports Football Club. Where the experimental approach was used to suit the current research, and the research community consisted of the players of the two clubs and the number of 44 players, and the research sample consisted of 24 players who were selected in a deliberate way, and the stability sample reached 10 players, while the sample of the survey experience reached 8 players who were excluded from the main experiment. The researchers designed the psychological counseling program according to previously monitored data, which were represented by specific needs and in line with these needs that were reached through the pre-test, which indicated a decrease in the level of sports cohesion among the players, and the results showed the superiority of the experimental group over the control in the post-test of sports cohesion After applying the program. The results showed that the psychological counseling program to enhance sports cohesion of football players had a favorable effect on the development of certain motor abilities and basic football skills in junior players. The players of the Mosul Municipality and the Waves Football Club suffer from a low level of sports cohesion. The preparation processes that players receive do not contribute to psychological support. The psychological counseling program has proven effective in developing a level of sports cohesion for players. The superiority of the experimental group over the control group in the level of sport cohesion in the dimensional measurement.